INTEGRATING THE LISTEN-READ-DISCUSS (LRD) STRATEGY WITH WORDWALL TO IMPROVE JUNIOR HIGH SCHOOL STUDENTS’ READING COMPREHENSION - Prastyawati, Masita Eka; Setiyadi, Ag. Bambang; Suparman, Ujang (Universitas PGRI Sumatera Barat, 2025)
Abstract This study aimed to examine the effectiveness of integrating the Listen-Read-Discuss (LRD) strategy with Wordwall as a game-based learning in improving students’ reading comprehension. A quantitative approach with a cluster random sampling was used. The research was grounded in the constructivist theory of language learning, which emphasized active involvement and contextualization in text understanding. The subjects were two randomly selected seventh-grade classes from SMP PGRI 2 Sukadana, with one serving as the experimental group that received the integrated LRD and Wordwall treatment, and the other as the control group that used the original LRD strategy. Data were collected using pretests and posttests and were analyzed through an independent t-test. The results indicated that the experimental group made considerably greater improvements in reading comprehension scores compared to the control group. The statistical analysis showed a significance level from the 2-tailed test that was less than 0. 05 (p 0.001) and also, t-value is higher than t-table with the significance level of higher than 0.05 confirmed the effectiveness of the LRD and Wordwall integration in enhancing vocabulary mastery, student engagement, and active classroom participation. These results supported the incorporation of interactive learning tools as a complement to original strategies in English language instruction.Keywords: Game-based learning, Listen-Read-Discuss, Wordwall, reading comprehension, vocabulary